2021
DOI: 10.1002/hep.31921
|View full text |Cite
|
Sign up to set email alerts
|

Lenvatinib Targets FGF Receptor 4 to Enhance Antitumor Immune Response of Anti–Programmed Cell Death‐1 in HCC

Abstract: BaCKgRoUND aND aIMS:Recently, clinical trials of lenvatinib plus pembrolizumab in HCC have displayed an impressive objective response rate. This study aimed to clarify the mechanism for optimal patient selection.appRoaCH aND ReSUltS: First, in patients with HCC, lenvatinib-treated recurrent tumors had lower programmed death ligand 1 (PD-L1) expression and regulatory T cell (Treg) infiltration compared with matched primary tumors. Consistently, in C57BL/6 wild-type mice receiving antiprogrammed cell death 1 (PD… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
142
1
2

Year Published

2021
2021
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 196 publications
(151 citation statements)
references
References 40 publications
(51 reference statements)
6
142
1
2
Order By: Relevance
“…The combined use of lenvatinib and ICB to promote CD8 + T cell infiltration and inhibit the number and function of Tregs, M2 macrophages, or MDSCs (in terms of IL10 or TGF-β secretion) has been confirmed in murine models of LIHC (Kimura et al, 2018;Kudo, 2019), COAD (Kato et al, 2019), and THCA (Gunda et al, 2019). Lenvatinib can also reduce tumor PD-L1 level to improve anti-PD-1 efficacy by blocking FGFR4 (Yi et al, 2021). The mechanisms of action of lenvatinib include (Figure 6): downregulating the expression of PD-1, CTLA-4, and TIM3 in T cells; blocking the binding of VEGFA and bFGF to their receptors, thereby inhibiting T-cell exhaustion (Deng et al, 2020); and destroying tumor cells, leading to the release of tumor antigens, which in turn promotes IFN-γ-mediated antigen presentation (Kato et al, 2019) and enhances the cytotoxicity of natural killer cells (Zhang et al, 2019).…”
Section: Discussionmentioning
confidence: 95%
“…The combined use of lenvatinib and ICB to promote CD8 + T cell infiltration and inhibit the number and function of Tregs, M2 macrophages, or MDSCs (in terms of IL10 or TGF-β secretion) has been confirmed in murine models of LIHC (Kimura et al, 2018;Kudo, 2019), COAD (Kato et al, 2019), and THCA (Gunda et al, 2019). Lenvatinib can also reduce tumor PD-L1 level to improve anti-PD-1 efficacy by blocking FGFR4 (Yi et al, 2021). The mechanisms of action of lenvatinib include (Figure 6): downregulating the expression of PD-1, CTLA-4, and TIM3 in T cells; blocking the binding of VEGFA and bFGF to their receptors, thereby inhibiting T-cell exhaustion (Deng et al, 2020); and destroying tumor cells, leading to the release of tumor antigens, which in turn promotes IFN-γ-mediated antigen presentation (Kato et al, 2019) and enhances the cytotoxicity of natural killer cells (Zhang et al, 2019).…”
Section: Discussionmentioning
confidence: 95%
“…Previous studies also indicated that lenvatinib could strongly inhibit the activation of ERK, the downstream signaling molecules of FGFR4, compared with sorafenib and regorafenib [ 32 ], and high FGFR4 levels (positive immunohistochemistry >10% of tumor cells) were an independent predictor of a response to lenvatinib [ 33 ]. Moreover, lenvatinib enhanced the antitumor immune response of anti-programmed cell death-1 (PD-1) in HCC by blocking FGFR4 [ 34 ]. However, lenvatinib alone could inhibit HCC cancer stem-like cells through FGFR1-3 signaling, but not FGFR4 signaling [ 35 ].…”
Section: Discussionmentioning
confidence: 99%
“…LEN significantly decreased the population of tumor-associated macrophages, as well as increased the percentage of activated CD8+ T cells secreting interferon-γ+ and granzyme B ( 24 , 25 ). In addition, LEN significantly reduced the level of tumor programmed death-ligand 1 (PD-L1) and Treg differentiation, improved anti-PD-1 efficacy by blocking FGFR4, and inhibiting TGFß signaling ( 26 , 27 ). The extent to which combination therapies pose clinical safety and tolerability challenges, and whether these challenges will limit their usefulness as an anticancer therapy, have been the focus of an increasing number of studies.…”
Section: Discussionmentioning
confidence: 99%